2018
DOI: 10.5194/acp-18-8293-2018
|View full text |Cite
|
Sign up to set email alerts
|

Sources and characteristics of summertime organic aerosol in the Colorado Front Range: perspective from measurements and WRF-Chem modeling

Abstract: Abstract. The evolution of organic aerosols (OAs) and their precursors in the boundary layer (BL) of the Colorado Front Range during the Front Range Air Pollution and Photochemistry Éxperiment (FRAPPÉ, July-August 2014) was analyzed by in situ measurements and chemical transport modeling. Measurements indicated significant production of secondary OA (SOA), with enhancement ratio of OA with respect to carbon monoxide (CO) reaching 0.085 ± 0.003 µg m −3 ppbv −1 . At background mixing ratios of CO, up to ∼ 1.8 µg… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 95 publications
1
10
0
Order By: Relevance
“…The bias is likely driven by a variety of factors that need to be explored on a regional basis. For instance, a previous model 445 analysis of FRAPPE observations over Colorado suggested that an underestimate of anthropogenic emissions from the oil and gas sector contributed to an underestimate of ASOA in the region (Bahreini et al, 2018). Both schemes over-estimate OA loadings in the northern latitudes (over parts of Alaska and Canada), likely due to an overestimate in POA from fires ( Fig.…”
Section: Evaluation Of Model Simulations Against Airborne Measurementsmentioning
confidence: 90%
“…The bias is likely driven by a variety of factors that need to be explored on a regional basis. For instance, a previous model 445 analysis of FRAPPE observations over Colorado suggested that an underestimate of anthropogenic emissions from the oil and gas sector contributed to an underestimate of ASOA in the region (Bahreini et al, 2018). Both schemes over-estimate OA loadings in the northern latitudes (over parts of Alaska and Canada), likely due to an overestimate in POA from fires ( Fig.…”
Section: Evaluation Of Model Simulations Against Airborne Measurementsmentioning
confidence: 90%
“…The campaigns are also influenced by different OA sources depending on their sampling region. The EUCAARI campaign over western Europe (Morgan et al, 2010), KORUS-AQ over the Korean Peninsula (Nault et al, 2018), CalNex over California (Ryerson et al, 2013), and DC3 (Barth et al, 2014) and FRAPPE over the central US (Dingle et al, 2016) sample over regions that are heavily influenced by anthropogenic emissions. In contrast, the GoAmazon campaigns during the wet and dry seasons (Martin et al, 2016;Shilling et al, 2018) over the Manaus region in the Amazon and the OP3 campaign (Hewitt et al, 2010) over equatorial forests in southeast Asia are heavily influenced by biogenic emissions, although the GoAmazon campaign in the dry season is also strongly influenced by biomass burning.…”
Section: Coefficient Of Determinationmentioning
confidence: 99%
“…Many of those studies suggest that the model-measurement discrepancies and differences among emission inventories approach a factor of two or more. To represent anthropogenic emissions during weekdays and weekend, the simulation uses the National Emission Inventory (NEI-2011), version 2 which correct VOC speciation profiles for oil and gas sources (Bahreini et al, 2018;McDonald et al, 2018). A Sunday emission inventory was used to represent the Monday of 2 September, which was the U.S. Labor Day holiday.…”
Section: Model Configurationmentioning
confidence: 99%